cGAS-STING pathway as a potential trigger of immunosenescence and inflammaging - Schmitz, Carine Raquel Richter; Maurmann, Rafael Moura; Guma, Fatima T. C. R.; Bauer, Moisés Evandro; Barbé-Tuana, Florencia Maria (Frontiers in Immunology, 2023)
Aging is associated with an increased incidence of autoimmune diseases, despite the progressive decline of immune responses (immunosenescence). This apparent paradox can be explained by the age-related chronic low-grade systemic inflammation (inflammaging) and progressive dysregulation of innate signaling. During cellular aging, there is an accumulation of damaged DNA in the cell’s cytoplasm, which serves as ubiquitous danger-associated molecule, promptly recognized by DNA sensors. For instance, the free cytoplasmic DNA can be recognized by the DNA-sensing cGAS-STING (cyclic GMP-AMP synthase linked to a stimulator of interferon genes), triggering transcriptional factors involved in the secretion of pro-inflammatory mediators. However, the contribution of this pathway to the aging immune system remains largely unknown. Here, we highlight recent advances in understanding the biology of the cGAS-STING pathway, its influence on senescence-associated secretory phenotype (SASP), and its modulation of the immune system during sterile inflammation. We propose this important stress sensor of DNA damage is also a trigger of immunosenescence and inflammaging.